FACTORS EFFECTING GENERATION Z’ FINANCIAL WELL-BEING IN EAST KALIMANTAN - Angelina Pilipus; Joyce A. Turangan (Graduate Program of Universitas Tarumanagara, 2026)
Financial well-being has become an increasingly important aspect of personal stability, particularly among Generation Z, who are highly engaged with digital financial systems and online economic activities. This study examines the influence of several key financial-related factors on the financial well-being of Generation Z in East Kalimantan. A quantitative approach was applied using an online survey administered to 219 respondents aged 18–27 years who met the established sampling criteria. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that all examined factors have a positive and significant effect on financial well-being. These results highlight the importance of strengthening financial understanding, improving access to financial services, and encouraging responsible financial practices to enhance the financial well-being of Generation Z.